Analisis Determinan Perilaku Ibu Dalam Mengatasi Stressor Pada Anak Usia Pra Sekolah (3-6 Tahun) Terhadap Dampak Hospitalisasi - Rhipiduri Rivanica; Neni Riyanti (Universitas Aisyiyah Yogyakarta, 2017)
This research use cross sectional research design. Using primary data. Result of univariate analysis from 87 respondents, it is known that the distribution of age frequency variable with young cataract is 83.9%, work variables with category work as much as 72.4%, educational variables with low educational and medium-level category as much as 54.0%, good knowledge with good category as much as 75.9%, variable attitude with positive category as much as 77.0%, while the variable behavior of mothers with category overcome the impact of hospitalization in pre school children as much as 77.0%. Results of bivariate age variable with p-value=0.062 and job variables with p-value=0.575. It is recommended that when child care is introduced with nurses and doctors who will care for it, involving parents who plays an active role in child care and shows empathy as the main approach in reducing fear due to painful procedures.